ANALISA PENDIDIKAN PROFETIK NABI MUSA - Bari, Mohammad Miftahul; Fauziyah, Habibatun; Ningsih, Indri Purwati (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
Seeking knowledge is an obligation for all Muslims, this obligation was enshrined by Allah through the words of the Prophet Muhammad to Muslims from the womb until death. The existence of this command provides a very broad coverage, from all elements of the Muslim community, including ordinary people to prophets and apostles. There are many stories about the scientific adventures of the prophets and apostles that we can study, whether in the form of concrete data contained in the texts of the Koran and Hadith or historical stories put forward by scholars in several classical and contemporary books. The story above holds a lot of value and faith that can be taken as study material or other useful things. Therefore, it is interesting to study the story of the journey of knowledge from the prophet, Messenger of Allah, named Nabi Musa As, along with his companion, who traveled through several regions until then Allah met Prophet Khidir As.